Efficacy of Sox10 Promoter Methylation in the Diagnosis of Intestinal Neuronal Dysplasia From the Peripheral Blood. Issue 12 (December 2019) - Liu, Yu-Rong; Ba, Fang; Cheng, Lan-Jie; Li, Xu; Zhang, Shi-Wei; Zhang, Shu-Cheng
Abstract : OBJECTIVES: Intestinal neuronal dysplasia (IND) is a common malformation of the enteric nervous system. Diagnosis requires a full-thickness colonic specimen and an experienced pathologist, emphasizing the need for noninvasive analytical methods. Recently, the methylation level of the Sox10 promoter has been found to be critical for enteric nervous system development. However, whether it can be used for diagnostic purposes in IND is unclear. METHODS: Blood and colon specimens were collected from 32 patients with IND, 60 patients with Hirschsprung disease (HD), and 60 controls. Sox10 promoter methylation in the blood and the Sox10 expression level in the colon were determined, and their correlation was analyzed. The diagnostic efficacy of blood Sox10 promoter methylation was analyzed by receiver operating characteristic curve. RESULTS: The blood level of Sox10 promoter methylation at the 32nd locus was 100% (90%–100%; 95% confidence interval [CI], 92.29%–96.37%) in control, 90% (80%–90%; 95% CI, 82.84%–87.83%) in HD, and 60% (50%–80%; 95% CI, 57.12%–69.76%) in IND specimens. Sox10 promoter methylation in the peripheral blood was negatively correlated with Sox10 expression in the colon, which was low in control, moderate in HD, and high in IND specimens (r = −0.89). The area under the curve of Sox10 promoter methylation in the diagnosis of IND was 0.94 (95% CI, 0.874–1.000, P = 0.000), with a cutoff value of 85% (sensitivity, 90.6%; specificity, 95.0%). By applying a cutoff value of 65%, promoter methylation was more indicative of IND than HD. DISCUSSION: The analysis of Sox10 promoter methylation in the peripheral blood can be used as a noninvasive method for IND diagnosis.